2015
DOI: 10.1007/978-981-287-643-0_9
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Reuse of Textile Effluent Sludge

Abstract: In the whole world today there has been a growing awareness of the damage caused to the environment by the haphazard use of chemicals, some of which are very poisonous and carcinogenic. The textile industry has been strongly criticised as being one of the world's worst lawbreakers in terms of pollution because it demands a large amount of water and chemicals. Although air, water, and noise pollution are created at every step of fabric treatment, the most problem-filled is fabric wet processing, in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 66 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…Hence, it can be concluded that the adsorption of P.TS onto BC is higher at low pH due to electrostatic attraction. Similar behavior was observed for adsorptions of azo disperse dye when increasing the pH from 1.0 to 7.0, resulting in a decrease of removal efficiency by Tezcan Un et al. (2015) and Wang et al.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Hence, it can be concluded that the adsorption of P.TS onto BC is higher at low pH due to electrostatic attraction. Similar behavior was observed for adsorptions of azo disperse dye when increasing the pH from 1.0 to 7.0, resulting in a decrease of removal efficiency by Tezcan Un et al. (2015) and Wang et al.…”
Section: Resultssupporting
confidence: 74%
“…The OH stretching vibration appearing at 3300–3450 cm −1 was attributed to the presence of phenols, alcohols, and carboxylic group. Also, the fact that this band is wide may be due to the presence of adsorbed water (Patel et al., 2015). The C = O and C = C stretching vibrations of protein and collagen on bovine bone are present in the 1500–1600 cm −1 range (Bedin et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations